Performance Testing and Optimization of DiTenun Website - Arlinta Christy Barus; Sinambela, Eka Stephani; Purba, Ivani; Simatupang, Jhonathan; Marpaung, Monika; Pandjaitan, Nancy (PT Mattawang Mediatama Solution, 2022)
DiTenun website is a web-based application developed to create new motifs or new weaving patterns. This website needs to have good performance so that it can be optimally used by the users. By understanding the importance of the information available on the DiTenun website, a performance testing is necessary. This performance test aims to verify specific system performance such as response time and service availability despite receiving a large number of requests. The performance analysis of the DiTenun website was carried out by spike testing using the Apache JMeter tool. In solving the problems and improving the performance of the DiTenun website, the researcher applied website optimization by utilizing the browser cache, activating gzip compression, and eliminating rendering – blocking resources. Evaluation of each solution was carried out by using a hypothesis test, namely using a paired sample t test. The result of the test showed that each solution that was implemented can be used to improve performance in the form of load time of the DiTenun website.